Improved reliability assessment of backup battery storage integrated with power supply system in a building - Othman, Muhammad Murtadha; Mohd Jamaluddin, Muhammad Amirul Naim; Fauzi, Faisal; Musirin, Ismail; Othman, Mohammad Lutfi (Institute of Advanced Engineering and Science (IAES), 2019)
This paper presents the improved analysis of reliability for battery storage used in power system. The reliability assessment of this paper includes the evaluation of reliability of the system components, battery module and power electronic components. Battery storage is considered as one of energy storage and energy source that commonly used in power system. The evaluation of the reliability of power systems utilising with the storage batteries is performed by using the Markov chain process. The computation of the reliability is conducted by referring to the generated reliability block begins from power supply system. Every part of the system is evaluated regarding two specific states that are in normal or failure mode. By using the Markov method, the system unavailability and failure frequency can be computed.